The Relationship of Muhadharah Activities with Student Learning Outcomes in the Akidah Akhlak Subject - Hikam, Bahrul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The aim of this research is to determine the relationship between muhadharah activities and student learning outcomes in akidah and morals subjects at Madrasah Tsanawiyah Daarul Ahsan Tangerang. Because Akidah Akhlak is a foundation or basis that must be instilled in students in order to become ethical and civilized. humans in their daily lives. This research uses a quantitative descriptive approach. Researcher using correlational methods (methods that look for relationships or correlations between the variables being searched for) which are supported by data and facts through questionnaires/questionnaires distributed. The population taken was all students of Madrasah Tsanawiyah (MTs) Daarul Ahsan Tangerang, totaling 150 people. Regarding sampling techniques, the author uses the